Future palliative competence needs – a qualitative study of physicians’ and registered nurses’ views - Arja Suikkala (BMC, 2021)
Abstract Background Globally, the need for palliative care will increase as a result of the ageing of populations and the rising burden of cancer, non-communicable diseases as well as some communicable diseases. Physicians and registered nurses working in palliative care should have a sufficient level of education and competence in managing the changing needs and requirements of palliative care. There is, however, need for evidence-based palliative care training and education of physicians and registered nurses. The purpose of this study was to describe the views of physicians and registered nurses regarding future competence needs within palliative care. Methods The study was conducted through use of a cross-sectional qualitative design. A total of 54 physicians and 110 registered nurses completed an open-ended questionnaire about the future competence needs of palliative care. The data were analyzed using inductive content analysis. Results The results revealed four main competence needs within palliative care for the coming decade: palliative care competence at all levels within healthcare and social welfare services; individualized palliative care competence; person-centered encounters competence; and systematic competence development within palliative care. Conclusions The results offer cues for education and professional development, which can be used to support physicians and registered nurses when future palliative care competences are included in educational programs. Seamless cooperation between palliative care services and educational institutions is recommended to ensure that undergraduate and postgraduate education is based on a continuous assessment of competence requirements within the field of palliative care. Therefore, online multi-professional simulations, for example, could be used to enhance future competencies within palliative care; undergraduate medical, nursing and allied healthcare students as well as postgraduate palliative care professionals and experts of experience could work together during simulations.